Comparative analysis of hemodynamic monitoring with pulmonary artery catheter and transthoracic echocardiography in patients with cardiogenic shock - V. V. Ryabov; A. G. Syrkina; M. A. Kercheva; I. I. Yolgin; O. O. Panteleev (Российский кардиологический журнал)
Aim. To compare main central hemodynamic parameters obtained by pulmonary artery catheterization and transthoracic echocardiography (TTE).Material and methods. This prospective study included 20 patients with acute myocardial infarction complicated by true cardiogenic shock. In all patients, number of central hemodynamic parameters was measured using a Swan-Ganz catheter and TTE. Comparison of both methods was carried out by Spearman correlation analysis and Bland-Altman plots using the STATISTICA 8.0 program.Results. We found quite a lot of agreement between the parameters measured by the two methods in the same patient at approximately the same time. Thus, the cardiac index (CI) is well measured by both methods. At the same time, the correlation coefficient was significantly higher when measuring CI using VTI (r=0,81 vs r=0,81) compared to LV volumes. Therefore, we consider the first method to be preferable. The values of total peripheral vascular resistance (TPVR), estimated by right atrial pressure, did not reveal agreement between methods. At the same time, there was agreement in case of central venous pressure. Measurement of pulmonary wedge pressure did not show agreement in me thods. We believe that this is due to the fact that diastolic function assessment in intensive care patients in the focal TTE mode may be difficult and not sufficiently correct.Conclusion. TTE can be used to monitor central hemodynamics in cases of satisfactory and moderately reduced cardiac imaging. Both the results of CI measurement using the Bernoulli formula and left ventricular volumes, as well as measuring TPVR using central venous pressure, are statistically consistent. Measurement of TPVR using right atrial pressure and measurement of pulmonary wedge pressure did not demonstrate agreement between the different techniques. We believe that TTE can be used to monitor CI and TPVR in patients with myocardial infarction complicated by true cardiogenic shock.